2011
DOI: 10.1016/j.jcrs.2011.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial cell loss during phacoemulsification: Bevel-up versus bevel-down phaco tip

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 19 publications
(24 reference statements)
1
38
0
Order By: Relevance
“…Preoperative parameters include older age, constricted pupil, firmness of the nucleus, and shorter axial length (AL) (1)(2) . Intraoperative factors include the incision size and design, Descemet membrane detachment, toxic intraoperative medications, phacoemulsification technique, and the type of ophthalmic viscosurgical device (OVD) used (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative parameters include older age, constricted pupil, firmness of the nucleus, and shorter axial length (AL) (1)(2) . Intraoperative factors include the incision size and design, Descemet membrane detachment, toxic intraoperative medications, phacoemulsification technique, and the type of ophthalmic viscosurgical device (OVD) used (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…presence of air bubbles, release of free radicals), low surgeon experience, and postoperative inflammation (3)(4)(5)(6) . To reduce the energy applied, aspects related to the phacoemulsifier such as ultrasound modes, special tips, microprocessors, and high-vacuum systems must be considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Faramarzi et al 1 reported on bevel-up versus bevel-down phaco tip during phacoemulsification. We disagree with the authors that it was the first study to consider this subject.…”
mentioning
confidence: 99%
“…Using the stop-and-chop technique, Faramarzi et al 1 concluded that better occlusion of the phaco tip with the bevel-down position and fear of posterior capsule damage may force placement of the phaco tip close to the posterior surface of the cornea, leading to endothelial cell damage. We used the phaco chop technique 5 and concluded that the bevel-down tip position had fewer negative effects on the corneal endothelium and facilitated attachment of the lens fragments.…”
mentioning
confidence: 99%